Estimation of The Time of Death Using Newton’s Law Cooling - Nor Afiza Ramli,; Cik Sri Mazzura Muhammad Basri , (Enhanced Knowledge in Sciences and Technology, 2022)
The determination of the time of death is essential to forensic investigation since the time of death represents the presumed time of the offence occurred. Determining the time of death based on investigations of the body still offers great difficulties in forensic science and it is one of the most popular issues especially in the investigation of criminal or suspicious deaths and civil cases. It is relevant in civil law to determine the order of inheritance in case there are multiple deaths occurred among family members at the same time, and it may cause a problem to the police and other law agencies in carrying out the investigations if not knowing the death time. Therefore, this research is to determine the time of death using Newton’s law of cooling model. In this study, three different cases taken from previous studies have been considered and used to predict the time of death. All cases are solved using Newton’s law of cooling model in order to determine the time of death and cooling period. Then, using MATLAB, the death time calculations and graphical representations of cooling are presented. Newton’s law of cooling graph shows that it is inversely proportional with the temperature difference between the body temperature and its surroundings and the time. In the beginning, the temperature drop is relatively fast, but it becomes slower as the body temperature decreases. This study can be concluded that this cooling model provides an approach to estimate the time when a crime or offence is committed.